2020
DOI: 10.18632/aging.103111
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the 8th edition of the American Joint Committee on Cancer Pathological Prognostic Staging for young breast cancer patients

Abstract: Purpose: This study aimed to validate the newly proposed American Joint Committee on Cancer (AJCC) pathological prognostic staging system for young breast cancer patients (aged ≤40 years). Results: We included 12811 women in this study. Overall, 52.8% of patients in the 7th AJCC stages were restaged to the 8th AJCC pathological staging system, including 10.7% upstaged and 42.1% downstaged. The receiver operating characteristics analysis showed that the new staging system had a better role in predicting breast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 38 publications
(60 reference statements)
3
2
1
Order By: Relevance
“…Our study shows that 149,452 (39.7%) individuals with BC migrated from the AJCC AS to AJCC PPS, which was similar to the rates observed in previous studies (20.7%-52.8%) [10,[18][19][20][21][22]. The downstaging rate was significantly higher than upstaging rate (33.7% vs 6.0%) in this study, and the results are consistent with those of previous studies (downstaging: 15.2%-42.1%; upstaging: 5.5%-41.0%) [10,[18][19][20][21][22]. Change in stage leads to diverse therapeutic decisions.…”
Section: Discussionsupporting
confidence: 90%
“…Our study shows that 149,452 (39.7%) individuals with BC migrated from the AJCC AS to AJCC PPS, which was similar to the rates observed in previous studies (20.7%-52.8%) [10,[18][19][20][21][22]. The downstaging rate was significantly higher than upstaging rate (33.7% vs 6.0%) in this study, and the results are consistent with those of previous studies (downstaging: 15.2%-42.1%; upstaging: 5.5%-41.0%) [10,[18][19][20][21][22]. Change in stage leads to diverse therapeutic decisions.…”
Section: Discussionsupporting
confidence: 90%
“…The American Joint Committee on Cancer's 8th edition of the Breast Cancer TNM Staging System is widely used for staging and prognostic assessment of breast cancer [20,22]. Consistent with many previous studies, the prognosis of breast cancer patients worsens as the tumor stage advances [21,23,24]. Our research has yielded similar results; the prognosis of breast cancer patients deteriorates with the progression of tumor stages, regardless of whether the patients have undergone anti-tumor treatment.…”
Section: Discussionsupporting
confidence: 89%
“…In our research, ROC curve analysis showed that the AUC value of the 7th AJCC stage was 0.683 (95%CI: 0.669–0.698, Fig 3A ), which was in the range of 0.620 to 0.728 previously studied [ 53 55 ]. The research conducted DeLong test on more than 60000 BC patients and found that the 10 ML algorithms had a better role in predicting the 5-year OS compared to 7th AJCC stage (all P < 0.001, Table 3 ).…”
Section: Discussionsupporting
confidence: 62%
“…For example, a study about the comparison of the prognostic accuracy of the 8th AJCC prognostic staging system to the 7th staging system using data from over 168000 BC patients confirmed the enhanced value of the 8th AJCC, while the latter still needed further improvement [ 56 ]. Furthermore, though several research results noticed that the AUC value of AJCC stage had risen from the 0.620–0.728 range of the 7th edition to the 0.670–0.773 range of the 8th edition [ 53 55 ], there was still a certain distance from the AUC value of MARS model in this study (AUC: 0.831, 95%CI: 0.820–0.842).…”
Section: Discussioncontrasting
confidence: 51%